APPLICATIONS OF COPPER-BASED FUNGICIDES AND INFESTATIONS OF Leucoptera coffeella (Guérin-Mèneville & Perrottet) IN COFFEE PLANTS - Sabino, Paulo Henrique Siqueira; da Silva, Gian Otavio Alves; da Silva, Adriano Bortolotti; Carvalho, Geraldo Andrade (Coffee Science - ISSN 1984-3909, 2019)
The present study aimed to evaluate the effects of applying fungicides with different sources of copper and of the number of applications on the occurrence of Leucoptera coffeella (Guérin-Menéville & Perrottet, 1842) (Lepidoptera: Lyonetiidae) and on the wax layer on leaves in a coffee plantation. Four applications of fungicides were carried out and the effects on the number of leaves mined by the insect and on the wax content on the leaf surface were evaluated. The copper-based fungicides increased the number of leaves mined by the leaf-miner and reduced the wax content on the coffee leaf surfaces in both periods studied.